Characterization of Immune Cell Populations of Cutaneous Neurofibromas in Neurofibromatosis 1 - Kallionpää, Roope A. (Elsevier, 2025)
Cutaneous neurofibromas (cNFs) are characteristic of neurofibromatosis 1 (NF1), yet their immune microenvironment is incompletely known. A total of 61 cNFs from 10 patients with NF1 were immunolabeled for different types of T cells and macrophages, and the cell densities were correlated with clinical characteristics. Eight cNFs and their overlying skin were analyzed for T cell receptor CDR domain sequences, and mass spectrometry of 15 cNFs and the overlying skin was performed to study immune-related processes. Intratumoral T cells were detected in all cNFs. Tumors from individuals younger than the median age of the study participants (33 years), growing tumors, and tumors smaller than the data set median showed increased T cell density. Most samples displayed intratumoral or peritumoral aggregations of CD3-positive cells. T cell receptor sequencing demonstrated that the skin and cNFs host distinct T cell populations, whereas no dominant cNF-specific T cell clones were detected. Unique T cell clones were fewer in cNFs than in skin, and mass spectrometry suggested lower expression of proteins related to T cell-mediated immunity in cNFs than in skin. CD163-positive cells, suggestive of M2 macrophages, were abundant in cNFs. Human cNFs have substantial T cell and macrophage populations that may be tumor-specific.